WOMEN EMPOWERMENT DEPICTED IN GANGUBAI KATHIAWADI FILM: A FEMINIST APPROACH - marianus woda liru; Maksimilianus Doi; Atika Halima Tusadiah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Abstract This research adopts women's empowerment found in the film Gangubai Kathiawadi that focusing on female sex workers who are often marginalized by society. The study investigates two primary issues: the types of women empowerments and the techniques employed by the main character to empower herself, the sex workers, and their daughters. This study utilizes a descriptive qualitative method grounded in feminist theory and Mandal’s empowerment framework. The findings reveal that the film illustrates various forms of empowerment, including social, educational, and political empowerment. The main character employs empowering techniques, such as standing behind women, standing up for them, giving them confidence, and acting as a sister. The film serves as both a portrayal of women's struggle and a critique of patriarchal injustice. Keywords: Women Empowerment, Feminism, Sex Workers, Film, Gangubai